The European company, Volume 1 - Van Gerven, Dirk; Storm, Paul (Law practitioner series, 2006)
The European company ('SE') is a legal entity offering a European perspective for businesses, which became a reality on 8 October 2004. Its purpose is to allow businesses that wish to extend their activities beyond their home Member State to operate throughout the EU on the basis of a single set of rules and a unified management system. This book explains how to set up and organise a European company, and sets out the text of the relevant EC instruments that serve as its legal basis, as well as the national implementing legislation. It is essential for businesses and their advisers to understand the implementing legislation of the relevant Member States in deciding where to establish an SE. This book provides comprehensive coverage of such legislation in all Member States of the European Economic Area which have, as at 1 July 2005, implemented the Regulation containing the SE statute and the Directive on employee involvement in the SE.